The Influence of the Heat Treatment Temperatures in Calcium Phosphate Synthesis - Dos Santos, Marcio L. [UNESP]; Riccardi, Carla S. [UNESP]; Noronha, Anderson L. [UNESP]; Olyveira, Gabriel M. de [UNESP]; Filho, Edson A. [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Amer Scientific Publishers, 2014)
The aim of this work was to explore the use of economically viable sol-gel precursors to synthesize calcium phosphate, hydroxyapatite phase. The influence of heat treatment temperature was evaluated. The powders were calcined at different temperatures ranging from 300 to 600 degrees C. Chemical phase compositions were evaluated by X-ray diffraction (XRD), thermal analysis (TG-DTA/DSC) and diffuse reflectance Fourier transform infrared spectroscopy (DRIFTS). The hydroxyapatite phase was obtained above 500 degrees C. The morphology and particle size were analyzed by scanning electron microscopy (SEM). This work showed that hydroxyapatite (HA) can be obtained using a simple, fast and low-cost apparatus method at low temperature synthesis. It could be concluded that this method can be also applied to bioactive calcium phosphates coatings of implant surfaces.
Keywords: Calcium Phosphates; Sol-Gel Route; Precursors; Biomaterials; Heat Treatment